ANALYSIS OF FINGERPRINT BIOMETRICS IN DETERMINING STUDENT LEARNING STYLES IN PRIMARY SCHOOLS - Dwi Pita Reski; Andi Yuyung; Muhammad Irfan; Romansyah Sahabuddin; Lutfi, Lutfi (Bajang Institute, 2024)
This research aims to analyse the potential use of fingerprint biometrics in determining students' learning styles to maximise the effectiveness of the learning process in primary schools. Fingerprint biometrics is recognised as one of the technologies that can provide unique information about individual characteristics, including cognitive potential and learning styles. This research method was conducted by reviewing a number of relevant literature studies and using an experimental approach on students to determine the correlation between fingerprint patterns and their learning abilities. The results show that there is a correlation between certain types of fingerprint patterns and students' learning styles, which can then be used as a basis for designing more effective learning methods. Thus, the use of fingerprint biometrics offers an innovative approach in the field of education to tailor teaching methods to the individual needs of students